PENGARUH PENILAIAN KINERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN MELALUI EQUAL EMPLOYMENT OPPORTUNITY SEBAGAI VARIABEL INTERVENING PADA PT PG RAJAWALI I - Septina Rizki Lutfia Ulya (Jurnal Ilmiah Mahasiswa FEB, 2016)
The research aims to determine the effect of performance assessment and career development on employee work satisfaction through equal employment opportunity at PT PG Rajawali I. This study uses all population members as the samples and obtains 75 valid samples. Path analysis is utilized here to identify the extent to which the dependent variables directly or indirectly affect the independent variable through the intervening variable. The research instrument is assessed in terms of its validity and reliability, the hypotheses are tested by t-test, and the classical assumption by normality test. The result of the hypothesis test shows that performance assessment and career development variables have indirect impact on employee’s work satisfaction through equal employment opportunity. This suggests that employee’s work satisfaction at PT PG Rajawali I is likely to increase when the performance assessment and career development are well-implemented through equal employment opportunity. Out of all measured variables, career development gives the most dominant influence on the employee’s work-satisfaction at PT PG Rajawali I.Keywords: Performance Assessment, Career Development, Equal Employment Opportunity, Work Satisfaction, Human Resource Management.